Environmental samples of microplastics induce significant toxic effects in fish larvae. (January 2020) - Pannetier, Pauline; Morin, Bénédicte; Le Bihanic, Florane; Dubreil, Laurence; Clérandeau, Christelle; Chouvellon, Fannie; Van Arkel, Kim; Danion, Morgane; Cachot, Jérôme
Abstract: Microplastics (MPs) are present throughout aquatic ecosystems, and can be ingested by a wide variety of organisms. At present, the physical and chemical effects of environmental MPs on aquatic organisms are poorly documented. This study aims to examine the physiological and behavioral effects caused by fish consuming environmental microplastics at different life stages. MP samples were collected from beaches on three islands (Easter Island, Guam and Hawaii) located near the North and South gyres of the Pacific Ocean. Larvae and juveniles of Japanese Medaka were fed for 30 days with three doses of MPs (0.01, 0.1 and 1% w/w in fish food) approximate to the concentrations measured in moderately and heavily contaminated ocean areas. Ingestion of MPs by medaka larvae caused (variously) death, decreased head/body ratios, increased EROD activity and DNA breaks and, alterations to swimming behavior. A diet of 0.1% MPs was the most toxic. Two-month-old juveniles fed with 0.01% MPs did not exhibit any symptoms except an increase in DNA breaks. Our results demonstrate ingestion and mainly sublethal effects of environmental MPs in early life stages of fish at realistic MP concentrations. The toxicity of microplastics varies from one sample to another, depending on polymer composition, weathering and pollutant content. This study examines the ecological consequences microplastic build-up in aquatic ecosystems, more particularly in coastal marine areas, which serve as breeding and growing grounds for a number of aquatic species. Highlights: Medaka larvae and juveniles were fed with food spiked with environmental microplastics. Fish at both stages easily ingest microplastics. Environmental microplastic exposure induces sublethal effects on larval growth and behavior. Microplastic toxicity varies widely from one sample to another.